Ocena prehranskega stanja starejših v socialnovarstvenem zavodu - Urh, Nika (Obzornik zdravstvene nege, 2017)
Introduction: Nutrition is one of the factors that determine the quality of life of the elderly in a residential home. The purpose of the study was to investigate nutritional status and propose suggestions to improve nutrition among the elderly in a residential home. Methods: A quantitative descriptive research method was used. Analysed were the weekly menus in one of the Slovenian residential homes, performed an analysis of the actual nutrient intake and assessed the nutritional status of the elderly (n = 48). The nutritional status was assessed by means of the body mass index and the mini nutritional assessment tool. The participants included in the study had a diet without any special dietary adjustments. Results: The average energy value of weekly menus amounted to 8457 kJ (2021 kcal) per day. 17 nutrients deviated from the recommendations. Men (M) and women (W) statistically significantly differed in the proportion of residual fats (%M = 16 %, %W = 24 %, p = 0.036), cholesterol (%M = 15 %, %W = 26 %, p = 0.035), vitamin D (%M = 15 %, %W = 27 %, p = 0.017) and vitamin B12 (%M = 17 %, %W = 25 %, p = 0.016). The body mass index showed that none of the elderly included in the study was malnourished or in the class III obesity. Discussion and conclusion: The study confirmed the need for systematic monitoring of the elderly's quality of nutrition in a residential home. In order to provide the elderly with adequate nutritional care, the cooperation of an inter-professional team with the elderly and their family members is necessary.
Keywords: elderly; institucionalna oskrba; institutional care; jedilniki; menus; nutritional risk; prehranska ogroženost; starejši